Design of the functional requirements of a smartphone app for patients receiving oral antineoplastic agents: The e-OncoSalud® app. (January 2020) - Collado-Borrell, Roberto; Escudero-Vilaplana, Vicente; Ribed, Almudena; Anglada-Martínez, Helena; Martín-Conde, Maite; Herranz-Alonso, Ana; Codina-Jané, Carlos; Sanjurjo-Sáez, María
Objective: To design a mobile app based on the needs of the onco-hematological patient receiving oral antineoplastic agents. Methods: A multidisciplinary working group (pharmacy–oncology–hematology) was created to design the app. The study was developed in three phases: first, we analyzed the features of patients receiving oral antineoplastic agents. We then analyzed available apps for cancer patients. Finally, we designed the app's functionalities. Results: We included 51 patients with middle-advanced age (68.7 years (SD=10.7)). They were polymedicated (mean: 5.3 (SD = 2.7), with numerous drug–drug interactions and adverse effects (all patients presented adverse effects). We then analyzed 166 apps. Most apps had more than one use, the most frequent being information (39.8%) and diagnosis (38.6%). Ten apps (6%) were for registering and monitoring treatment and adverse effects. Almost half of the apps (48.8%) were developed by healthcare organizations. Finally, we designed an app (e-OncoSalud®) with the following functionalities: (a) agenda; (b) treatment and drug interactions checker; (c) continuous recording of self-controls (weight, blood pressure, general condition) and adverse effects. The management of the adverse effects are based on an algorithm which provides different recommendations according to the adverse effects severity; (d) patient–pharmacist messaging in real-time; (e) education. Conclusions: After analysis of the main problems affecting these patients and the needs not covered by the existing apps, we designed e-OncoSalud®. It integrates relevant information about their treatment, focused on drug interactions identification and the prevention, and management of adverse effects.